An ethics of sexual difference - Irigaray, Luce. (London : Continuum, 1993)
Luce Irigaray is the foremost feminine thinker on sexual difference of our times whose work ranges over philosophy, psychoanalysis, linguistics and social critique.
Includes bibliographical references.
AAL
Keywords: Sexual ethics; Feminist theory; Philosophy